Hermetic Technology A new beginning for grains storage and farmers benefit - Mann, Sandeep; Yeole, Nileshwari; Swine, Kishore; Mittal, Sachin (Indian Farming, 2020)
Hermetic bags are used for storage and preservation of grains and pulses for a long time. These bags help in extending germination of seeds, maintain stable seed weight and moisture content for extended periods. Most importantly, they control insect pest without use of any insecticides. Live insects in the bags have been observed to be dead after 1-2 weeks of storage. These bags are not much expensive than conventionally used bags. Hence, this technique would be one of the most effective and economical tool in reducing storage losses at the household and commercial levels as compared to traditional storage systems.